Compositional factors driving antibacterial efficacy in healthcare wet wipe products - Angulo-Pineda, Carolina; Lu, Jian Ren; Cartmell, Sarah; McBain, Andrew J. (Frontiers in Microbiology, 2025)
Healthcare-associated infections represent a persistent global pathogenic challenge, with surface contamination serving as a critical transmission vector. Antibacterial wet wipes are widely used in public health service settings, but their effectiveness varies depending on their composition and design. Evaluating existing products based on objective criteria provides a valuable foundation for enhancing future functional wet wipe formulations. In this study, four compositionally distinct proprietary antimicrobial wet wipes were assessed using objective criteria to provide a foundation for designing functional and biodegradable wet wipe formulations with enhanced properties. The mechanical properties, chemical composition, surface tension, disinfectant release, and morphological structure of four widely used wet wipe products in UK and European healthcare settings were evaluated. These products are anonymised as HP (containing oxidizing agents), BDB, DPA, and ADM (based on quaternary ammonium compounds). Antibacterial performance was tested according to EN 16615, EN 13727, and ASTM E2967 standards (suspension and wiperator-based methods) using contact times of 30 and 60 s, against E. coli, S. aureus, MRSA, and A. baumannii. The BDB product underperformed in the analysis based on the EN 16615 standard, particularly at the short contact time, where it was ineffective against E. coli and S. aureus. In contrast, HPE, DPA, and ADM products demonstrated high efficiency, achieving >5 Log bacterial reduction within 60 s for all tested strains. The ADM product demonstrated superior antibacterial performance, eliminating A. baumannii in the shortest contact time and avoiding spread of bacteria to clean surfaces. Our findings demonstrate a correlation between the liquid release rate of the wipe and the biocidal agents used, with effectiveness in reducing bacterial viability on surfaces. This research establishes a framework for optimizing disinfectant wipe design by emphasizing the importance of material properties and disinfectant formulation in determining overall effectiveness.